2012
DOI: 10.1089/dna.2012.1692
|View full text |Cite
|
Sign up to set email alerts
|

ThelL-8andIL-13Gene Polymorphisms in Inflammatory Bowel Disease and Colorectal Cancer

Abstract: Inflammatory bowel diseases (IBD) and colorectal cancer (CRC) are disorders that originate from immune disturbances. In our study, we evaluated the association between the -251 T/A interleukin (IL)-8 and the -1112 C/T IL-13 polymorphisms, the risk of IBD, and CRC development. Genotypes were determined by PCRrestriction fragment length polymorphism in 191 patients with CRC, 150 subjects with IBD, and 205 healthy controls. We found an association between CRC and the presence of the -251 TA genotype and A allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In the current study, we found that lentinan down‐regulated LPS‐induced TLR4‐mediated NF‐κB signalling pathway and the expression of various inflammatory cytokines, which are key factors in leucocyte extravasation, colitis and CAC . For example, it reduced the expression of IL‐13 and CD30L, which are two key factors in IBD and CAC . We suppose that the inflammation‐modulating properties of lentinan may vary depending on cell type and the inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 54%
“…In the current study, we found that lentinan down‐regulated LPS‐induced TLR4‐mediated NF‐κB signalling pathway and the expression of various inflammatory cytokines, which are key factors in leucocyte extravasation, colitis and CAC . For example, it reduced the expression of IL‐13 and CD30L, which are two key factors in IBD and CAC . We suppose that the inflammation‐modulating properties of lentinan may vary depending on cell type and the inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 54%
“…Table 1 shows the basic information from these studies.There were two hospitalbased studies and seven population-based studies. The genotype distribution of three studies (Kury et al, 2008;Mustapha et al, 2012;Walczak et al, 2012) did not conform to Hardy-Weinberg equilibrium expectations. However, the distribution of the genotype in overall control population was consistent with Hardy-Weinberg equilibrium (P > 0.05).…”
Section: An Allelic Model (A Versus T) Each Study Was Shown Bymentioning
confidence: 68%
“…the point estimate of the OR (the size of the square is proportional to the weight of each study) and 95% CI for the OR (extending lines); the pooled OR and 95% CI were shown by diamonds Tsilidis et al, 2009;Mustapha et al, 2012;Walczak et al, 2012) including 3,019 cases and 3,984 controls comparing the IL-8 T251A polymorphism and colorectal cancer susceptibility were identified based on MOOSE (Meta-analysis of Observational Studies in Epidemiology) guidelines (Stroup et al, 2000). Table 1 shows the basic information from these studies.There were two hospitalbased studies and seven population-based studies.…”
Section: An Allelic Model (A Versus T) Each Study Was Shown Bymentioning
confidence: 99%
“…Moreover, −251A polymorphisms are thought to increase susceptibility to the development of gastric cancer and IBD. [110][111][112][113][114] It is worth noting that the reproducibility of some of the above studies has been questioned. As a result, it has been postulated that the presence of these mutations may influence the development of GI disease only within certain populations.…”
Section: Cxcl8 Gene Polymorphismsmentioning
confidence: 99%